The role of school violence in teacher career dropout: a proposal for an analytical matrix (Educação e Pesquisa, 2022)
School violence has been a research topic in Brazil since the 1980’s and it is one of the main challenges the national education system faces. The central objective of this article is to discuss the role of the experiences of school violence in the abandonment of the teaching career. To this end, we interviewed a former teacher who – as many others - had given up teaching after suffering emotional exhaustion due to the violence experienced at school. Based on literature and on the narrative inquiry of the former teacher’s reports, we considered it important to realize that school violence is an experience which is objectively regulated and subjectively experienced. While an objectively regulated reality, violence can be classified as a crime, incivility and symbolic violence. As a subjectively lived experience, we can distinguish various levels of trivialization that – in Arendt’s sense – designate the superfluity and the superficiality of the social relationships in totalitarian systems. Together, both dimensions – objective and subjective – constitute what we term as the school violence matrix, which is an analytical tool that is potentially useful for investigating how the violence can influence the paths of teaching professionals. Also, the results enabled us to understand how the several school agents (students, the principal and even the teacher) participate in the production of school violence and how the parties involved have conflicting perceptions. At last, implications for the teachers’ education are discussed.